Pendampingan Pengembangan Sistem Informasi AMI Berbasis PPEPP dengan Vibe Coding pada Program Studi Informatika UNIM - Ahmad Syaifuddin; Ronny Makhfuddin Akbar; Hafizh Fianto Putra; Yanuarini Nur Sukmaningtiyas; Anita (Jurnal Bakti Dirgantara, 2026)
Implementing the Internal Quality Assurance System (SPMI) via the PPEPP cycle is a mandatory requirement for study programs to align with LAM INFOKOM accreditation criteria. The assessment process is often hindered by the management of the Self-Evaluation Report (LED) and Internal Quality Audit (AMI) documentation, which still rely on manual, conventional filing methods. To address these issues, this community service initiative was organized to assist the quality assurance team in designing an integrated management information platform. The innovative approach adopted for this software development is "vibe coding" leveraging artificial intelligence as a virtual assistant to accelerate code syntax generation. The system's data architecture and logic were developed using a PHP framework, while the user interface design utilized the flexibility of Tailwind CSS. The project outcomes confirm that the application of vibe coding drastically reduced the time required to build the application. This system enables the quality assurance team to conduct simulated assessments using LAM INFOKOM instruments much more efficiently, a success reflected in a high user satisfaction index of 94.4%. Furthermore, the series of technical assistance sessions, combined with Focus Group Discussions (FGDs), proved effective